1989
DOI: 10.1111/j.1365-2559.1989.tb02166.x
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of oesophagitis by histology and morphometry

Abstract: Morphometric measurements of nuclear area, nuclear concentration and nucleolar dimensions in defined tissue zones of orientated oesophageal biopsy sections were compared between three patient groups--asymptomatic/normal endoscopy (n = 8); symptomatic reflux/normal endoscopy (n = 17); and symptomatic/endoscopic oesophagitis (n = 15). No significant differences could be shown for any mean parameter between clinical groups. In a further group of 16 patients, identical morphometric measurements were made in non-or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0
2

Year Published

1992
1992
2012
2012

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 8 publications
0
7
0
2
Order By: Relevance
“…This allows potential application in routine histological diagnosis. An advantage of ISD as a diagnostic tool for GERD stems from the fact that it does not require proper orientation of the mucosa in histological sections, a strict requirement for the assessment of papillae elongation and basal cell hyperplasia [14] which proved difficult to fulfil in routine grasp biopsies [4,16]. In addition, we found no substantial difference between the results of biopsies taken at different distances from the squamo-columnar junction, a factor which has been suggested to affect the specificity of other histological tools [31].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This allows potential application in routine histological diagnosis. An advantage of ISD as a diagnostic tool for GERD stems from the fact that it does not require proper orientation of the mucosa in histological sections, a strict requirement for the assessment of papillae elongation and basal cell hyperplasia [14] which proved difficult to fulfil in routine grasp biopsies [4,16]. In addition, we found no substantial difference between the results of biopsies taken at different distances from the squamo-columnar junction, a factor which has been suggested to affect the specificity of other histological tools [31].…”
Section: Discussionmentioning
confidence: 99%
“…The diagnostic value of these findings has been the subject of many investigations leading to conflicting results [4,25,30]. In general, histological lesions were well represented in the esophageal mucosa, showing erosive esophagitis at endoscopy.…”
Section: Introductionmentioning
confidence: 99%
“…All oesophageal biopsies were assessed for the presence or absence of intra-epithelial eosinophilic and neutrophilic granulocytes, lymphoid cells, mast cells, basal cell hyperplasia, elongation of the papillae, microscopic erosion or necrosis, and columnar metaplasia [31,32]. For the assessment of 'basal cell' hyperplasia, the cytologic criteria of choice were those devised by Jarvis et al [33] (nuclear size and crowding, prominence of nucleoli and cytoplasmic basophilia of the basal as well as of the intermediate layers of the epithelium) because, unlike other, more commonly used criteria [34] [35].…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, this combination has been regarded as an unspecific normal variant [14][15][16][17]. It has been demonstrated that antacids [18] and H 2 blockers [19] do not lead to changes in basal cell hyperplasia and length of papillae.…”
Section: Introductionmentioning
confidence: 99%